Choose your own Nick: a collection of stories - Seyedbagheri, Mir-Yashar, author; Doenges, Judy, advisor; Levy, EJ, committee member; Alexander, Ruth, committee member (Colorado State University. Libraries, 2018)
The six stories in Mir-Yashar Seyedbagheri's thesis, "Choose Your Own Nick" explore character development through the prism of one character in a plethora of what if scenarios. The stories seek to develop an understanding of how particular environments impact character's decisions. In six different stories, the same character reacts differently, with a myriad of consequences. In "Secret Love" a young man grapples with the ramifications of his sister's death. In "Operation Hero Nick," a character fakes his own death to get money for his struggling sister. And in the title story, "Choose Your Own Nick," an MFA fiction student tries to examine his life through incarnations of himself. These stories ultimately illustrate that circumstances can have a detrimental impact with significant emotional impact on those who are successful and those who are struggling in life.